2010
DOI: 10.1016/j.ijpharm.2010.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal drug delivery by in-skin electroporation using a microneedle array

Abstract: The aim of the present work was to develop a minimally invasive system for the delivery of macromolecular drugs to the deep skin tissues, so-called in-skin electroporation (IN-SKIN EP), using a microneedle (MN) electrode array. Fluorescein isothiocyanate (FITC)-dextran (FD-4: average molecular weight, 4.3 kDa) was used as the model macromolecular drug. MNs were arranged to puncture the skin barrier, the stratum corneum, and electrodes were used for EP so that a high electric field could be applied to skin tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…The lipoplexes were unstable upon aggregation in the in vivo environment, especially in serum-containing environment due to the destabilization of vesicles, resulting in pDNA leakage from the carriers before reaching the target cells. 28 In the case 46 found that 48 h of exposure of the cell line dendrimers corresponded to ∼100% internalization efficiency of the tested concentrations. Moreover, the accumulation of radiolabeled dendrimers in mice was evaluated by Roberts et al, 47 and dendrimers accumulated in several organs over 48 h. These findings suggest that accumulation might occur because the expression process of dendrimer complexes did not complete within 24 h, and thus, transfection durations .24 h may be required.…”
Section: In Vivo Immunization Studymentioning
confidence: 95%
See 3 more Smart Citations
“…The lipoplexes were unstable upon aggregation in the in vivo environment, especially in serum-containing environment due to the destabilization of vesicles, resulting in pDNA leakage from the carriers before reaching the target cells. 28 In the case 46 found that 48 h of exposure of the cell line dendrimers corresponded to ∼100% internalization efficiency of the tested concentrations. Moreover, the accumulation of radiolabeled dendrimers in mice was evaluated by Roberts et al, 47 and dendrimers accumulated in several organs over 48 h. These findings suggest that accumulation might occur because the expression process of dendrimer complexes did not complete within 24 h, and thus, transfection durations .24 h may be required.…”
Section: In Vivo Immunization Studymentioning
confidence: 95%
“…27 Additionally, the combination of MN patches and EP induced a synergistic effect on macromolecule skin permeation compared with MNs alone or conventional EP. 28,29 However, until now, there has been a lack of publications on comparison of the effectivity of solid MN patches, EP patches, the combination of MN and EP patches, and hollow MNs for DNA vaccinations in skin both in vitro and in vivo.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The limiting factor for percutaneous absorption of a drug is the reservoir and penetration into the stratum corneum [1,2]. Therefore, penetration enhancement is an important task for modern dermatopharmacology [3][4][5].…”
Section: Introductionmentioning
confidence: 99%